Self‐Adaptive Reflectance Film for Passive Temperature Regulation in Diverse Environments - Shuo Yang; Sizhe Tang; Yufeng Cai; Zhiming Ye; Xiangbin Zou; Xueyu Yuan; Yujie Song; Bing Li; Dongyan Tang; Ming Liu (Advanced Science, 2025)
Abstract Passive thermal‐regulation strategies have become increasingly important due to the strain alleviated on power grids for temperature management. Designing a system capable of automatically switching between cooling and heating modes in response to changing ambient conditions presents several specific challenges that engineers and researchers are actively addressing. In this research, a CaCl2 incorporated PNIPAM coated fluorinated poly(aryl ether) (FPAE) porous film with tunable reflectance is developed. The aim is to mitigate the reliance on active cooling systems, which consume significant amounts of energy. The moisture‐temperature dual sensitive film exhibits a tunable reflectance range between 91.1% and 39.1% via phase change of the PNIPAM layer. Coupled with an infrared emissivity of 96.0%, a daytime cooling of 10 °C compared to the control experiment is achieved. Coating the film with a photothermal layer results in an adaptive Janus film that is capable of autonomous switching between heating and cooling, and demonstrates a heating of 22.5 °C in a cold environment. The facile preparation method, excellent cyclic stability, mechanical properties, and UL‐94 V‐0 rating enable promising applications of the smart film under diverse living environments.